Bulk organic geochemistry (TOC, TN, d13C, d15N) of 3 vertical profiles from Holocene volcanic ash soils in Chilean Patagonia - Sebastien Bertrand (PANGAEA, 2025)
This dataset presents bulk organic geochemical data (TOC, TN, d13C, d15N) obtained by EA-IRMS analysis on 108 samples from 3 vertical profiles from Holocene volcanic ash soils in Chilean Patagonia (44-48°S). The samples were collected in 2012 and 2013 at a vertical resolution of 5-10 cm. The samples were collected with a metal trowel, after cleaning the vertical profile with a shovel. They were dry-sieved <90 μm before analysis. The mineralogical and inorganic geochemical composition of the same samples was published in Vandekerkhove et al. (2016) and are available on Earthchem (doi:10.1594/IEDA/100526).